Revisiting the Dynamical Model for the Evolution of Hot Spots and Its Cosmological Application - Yalong Nan; Shuo Cao; Tao An; Haiyan Zhang; Wuzheng Guo; Ailing Zeng; Shiming Wen; Ruobing Ding (The Astrophysical Journal Supplement Series, 2025)
Compact symmetric objects (CSOs) typically refer to small-scale extragalactic radio sources (usually <1 kpc) that exhibit strong radio emission on both sides (hot spots) and have a symmetric morphology. In this paper, we revisit the dynamical model for the evolution of hot spots in powerful radio sources, based on the latest bona fide CSO sample with well-defined statistical characteristics. Specifically, we focus on the subsample of CSOs that exhibit edge brightening, high luminosity, and prominent hot spots, and furthermore derive their luminosity and linear sizes between tens to hundreds of parsecs. The luminosity–linear size relation highlights the significant potential of CSOs in the study of modern cosmology. Finally, we investigate the possibility of testing the dynamical hot spot model with a much higher accuracy using CSOs observed in future very long baseline interferometry surveys. It is shown that our method could provide an independent test of the cosmic distance duality relation, reinforcing the potential of CSOs acting as a reliable cosmological probe.